Perencanaan dan Pengendalian Bahan Baku Cup 220 ml Dengan Pendekatan Material Requirement Planning di PT Tirta Sukses Perkasa Sukorejo - M. Imron Mas'ud; Pratiwi, Dina Eka (2477 - 6165, 2023)
PT Tirta Sukses Perkasa is a manufacturing company engaged in the production of plastic for packing CLUB mineral water products. Based on initial observations, this company experienced problems in controlling raw materials, thereby reducing cost effectiveness and efficiency. The purpose of this study is to control and determine the amount of raw materials that must be provided. This study used a descriptive quantitative approach with 25 material populations. This study used purposive sampling with a total sample of 4 materials. Researchers here as research instruments that act as data collectors. The analysis method used is the Material Requirement Planning (MRP) method with the help of QM for Windows V5 software. Based on the research results, the MPS forecasting method uses the Moving Averages technique, because it has smaller MAD, MSE and MAPE values compared to using the Exponential Smoothing method. The most optimal Lot sizing uses the Lot for lot technique compared to using the EOQ method because it has a lower total inventory cost.